Zaduma nad życiem w pieśniach Bułata Okudżawy = Pondering upon life in the songs of Bułat Okudżawa - Jabłoński, Romuald Marek (1956- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study is an interpretation of "Prayer" and "Georgian song". In the first lyric one can notice thelink between sacral motif (for ex. Apostrophe to God, homage paid to God the Creator) and personalmotifs (wife` illness). One can also see in it elements of irony (requests addressed to God). It inducesone to reflect on the origin on an evil. In the other text the poet makes use of motifs connectedwith myths, beliefs, literature and Georgian art. He connects them with sacrum (deification of man,sacralization of love and friendship, trust in God`s merci). The study also points out the incoherencebetween the official poet`s declaration (atheism) and poetical practice (religious motifs).
Keywords: Okudžava, Bulat (1924-1997); Poezja rosyjska - motywy